Effect of commercial (vimang) and hydroalcoholic extract of Mangifera indica (Mango) on gentamicin-induced nephrotoxicity in rat - Abolfazl Khajavi Rad; Leila Ghazi; Mohammad Taher Boroushaki; Alireza Khooei; Zakieh Keshavarzi; Sara Hosseinian; Somayeh Shafiee; Shahrzad Havakhah (Mashhad University of Medical Sciences, 2011)
Objectives: Mangifera indica (Mango) is used in folk medicine for treatment of different types of diseases, and its anti-inflammatory and free radical scavenging activities have been demonstrated. The present study evaluated the effects of commercial (vimang) and hydroalcoholic extract of Mango on gentamicin-induced nephrotoxicity in rat. Materials and Methods: Female Wistar rats were treated with vimang (50 and 100 mg/kg) for 18 days, or hydroalcoholic extract (200 and 400 mg/kg) for 18 days as preventive groups and others with vimang (100 mg/kg) for 8 days, or hydroalcoholic extract (400 mg/kg) for 8 days as treatment groups and also gentamicin (GM) was used at 80 mg/kg/day for eight days, starting from day 10. At the end of treatment, blood and urine samples were taken for measurement of creatinine (Cr) and BUN. The kidney was prepared for histological evaluation. Results: Serum Cr and urea concentrations as well as renal tissue injury increased significantly in GM group compared with the control group. Hydroalcoholic extract of Mango at 200mg/kg was able to reduce plasma Cr and urea concentrations significantly as well as kidney tissue necrosis. Vimang (50 and 100 mg/kg) and hydroalcoholic extract of Mango (200mg/kg) also prevented kidney tissue damage compared with the control group. Conclusion: Mango products were able to improve kidney function in an established model of GM-induced nephrotoxicity in the rat. The beneficial effects of Mango on the rat kidney seem to be dose and time-dependent. However, more investigations are needed to elucidate Mango action on GM-induced renal toxicity.